3D supramolecular self-assembly of [60]fullerene hexaadducts decorated with triarylamine molecules. Issue 55 (22nd June 2018) - Gavat, Odile; Nguyet Trinh, Thi Minh; Moulin, Emilie; Ellis, Thomas; Maaloum, Mounir; Buhler, Eric; Fleith, Guillaume; Nierengarten, Jean-François; Giuseppone, Nicolas
Abstract : Multiple grafting of triarylamine subunits onto a hard-core C60 unit leads to three-dimensional networks of triarylamine-based supramolecular polymers. Abstract : A clickable fullerene hexa-adduct scaffold has been functionalized with twelve triarylamine subunits. The light-triggered self-assembly of this molecular unit leads to 3D honeycomb-like structures with inner pores of around 10 nm diameter. Multiple grafting of triarylamine subunits onto a hard-core C60 unit increases the dimensionality of the self-assembly process by reticulating the 1D nanowires typically obtained from the supramolecular polymerization of triarylamine monomers.